Mitochondrial DNA control region data reveal high prevalence of Native American lineages in Jujuy province, NW Argentina - Cardoso, Sergio (2013)
Mitochondrial control region (16024-576) sequences were generated from 180 individuals of four population nuclei from the province of Jujuy (NW Argentina), located at different altitudes above sea level. The frequency at which a randomly selected mtDNA profile would be expected to occur in the general population (random match probability) was estimated at 0.011, indicating a relatively high diversity. Analysis of the haplogroup distribution revealed that Native American lineages A2 (13.9%), B (56.7%), C1 (17.8%), D1 (8.9%) and D4h3a (1.1%) accounted for more than 98% of the total mtDNA haplogroup diversity in the sample examined. We detected a certain degree of genetic heterogeneity between two subpopulations located at different points along the altitudinal gradient (Valles and Puna), suggesting that altitude above sea level cannot be ruled out as a factor promoting divergences in mtDNA haplogroup frequencies, since altitude is closely associated with human living conditions, and consequently, with low demographic sizes and the occurrence of genetic drift processes in human communities. In all, mitochondrial DNA database obtained for Jujuy province strongly points to the need for creating local mtDNA databases, to avoid bias in forensic estimations caused by genetic substructuring of the populations.